A Comparison of Two Five-Factor Model Operationalizations of the Triarchic Model of Psychopathy in a Clinical Sample. (October 2022) - Ruchensky, Jared R.; Donnellan, M. Brent; Hopwood, Christopher J.; Edens, John F.; Skodol, Andrew E.; Morey, Leslie C.
Structural models of personality traits, particularly the five-factor model (FFM), continue to inform ongoing debates regarding what personality attributes and trait domains are central to psychopathy. A growing body of literature has linked the constructs of the triarchic model of psychopathy (boldness, meanness, disinhibition) to the FFM. Recently, researchers developed both item and regression-based measures of the triarchic model of psychopathy using the NEO Personality Inventory–Revised—a popular measure of the FFM. The current study examines the correlates of these two FFM-derived operationalizations of the triarchic model using data from the Collaborative Longitudinal Personality Disorders Study. The two approaches had strong convergent validity coefficients and similar patterns of criterion-related validity coefficients. Meanness related to greater personality pathology characterized by exploitation of others and poor attachment, whereas disinhibition related to indicators of greater negative affect and poor behavioral constraint. Boldness related to reduced negative affect and greater narcissistic personality traits. Although the item and regression-based approaches showed similar patterns of associations with criterion-variables, the item-based approach has some practical and psychometric advantages over the regression-based approach given strong correlations between the meanness and disinhibition scores from the regression approach.